USE OF TITANIUM NIKELIDE IMPLANT AND FREE REVASCULARIZED FLAP FOR RECONSTRUCTION OF FENESTRATED TRACHEAL DEFECT (EXPERIMENTAL INVESTIGATION) - E. B. Topolnitskiy (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Reconstruction of fenestrated tracheal defect using free revascularized flap combined with titanium nikelide implant has been developed. The experimental study was performed on 8 mongrels, on which defect or tracheostomy was created. The tracheal defect reconstruction was completed using free fasciocutaneous inguinal flap. Efficacy of the method was tested using clinical, radiological, macro- and microscopic examination. It is ascertained, that the technique permits to reconstruct fenestrated tracheal defect with minimal injury of donor zone, to simplify and shorten the operation.